The Implementation of Fieldwork Program Based Lesson Study to Improve Pedagogical Skills of Teachers and Students Learning Outcomes - ., Suparti; ., . (International Journal of Engineering and Technology, 2018)
The main purpose of this research was to explain how the implementation of Fieldwork Program (Praktik Pengalaman Lapangan/PPL) based lesson study can be improve pedagogical skills of teachers and students learning outcomes. The study was conducted based on basic question, how to improve teachersâ€™ skills and studentsâ€™ learning outcome. This research is a class action research that uses descriptive qualitative approach. The research is conducted in PGRI Vocational School in Malang, Indonesia, with 33 students (eleventh grade) and one teacher who became a model teacher. The instruments used in this research such as (1) the execution sheet of the lesson study steps which includes 3 steps such as plan, do, and reflection (see), (2) learning observation sheet, (3) teacher pedagogic skill assessment form that contains the assessment aspect as well as the teacher pedagogic indicator (PPL students) during learning process, (4) cognitive test questions used is quiz (post test), (5) supporting data such as studentsâ€™ responses questionnaire and field notes. The results showed that implementation of PPL based lesson study can improve pedagogical skills of teacher from 69,4 to 77,75 point. The increase of teachers pedagogical skills have an impact on students learning outcomes. Students learning outcome can be reflect on classical completeness class, raised from 68,73% to 87,96%. Based on these results can be concluded that the implementation of PPL based lesson study can improve teachers pedagogical skills and students learning outcomes. This research will strengthen the rationale for using lesson as an alternative method to increase teachersâ€™ skill (especially on pedagogical skill) and students learning outcome.Â Â